Elevated Interleukin-36α And CD4+IL-36α+T Cells Are Involved in the Pathogenesis of Graves' Disease - Yao, Qiu-ming; Li, Ling; Song, Zhen-Yu; Wang, Bin; Qin, Qiu; An, Xiao-fei; Zhang, Jin-an (Frontiers in Endocrinology, 2018)
Abstract Background: IL-36α is involved in the pathogenesis of a variety of autoimmune diseases, but the relationship between IL-36α and Graves’ disease (GD) has rarely investigated. In the present study, we aimed to explore the expression of IL-36α and elucidate the potential role of IL-36α in GD. Methods: The expression of IL-36α mRNA in peripheral blood mononuclear cells (PBMCs) from 32 newly diagnosed GD patients, 15 refractory GD patients and 30 normal controls (NC) was examined using quantitative real-time polymerase chain reaction (qRT-PCR). The level of IL-36α in serum from 46 newly diagnosed GD patients, 10 refractory GD patients and 24 NC was measured using enzyme linked immunosorbent assay (ELISA). The percentage of CD4+IL-36α+T cells was detected by flow cytometry. PBMCs from newly diagnosed GD patients and NC group were cultured in the presence or absence of recombinant human IL-36α, and the expression levels of IFN-γ, TNF-α, IL-6 and IL-17A in culture supernatant were detected by cytokine array. Results: The expression of IL-36α mRNA in newly diagnosed GD patients was significantly higher than that in NC group (P = 0.019). IL-36α mRNA expression was positively associated with thyrotropin receptor antibody (TRAb) (P = 0.004, r = 0.498) in newly diagnosed GD patients. The level of IL-36α in serum from newly diagnosed GD patients was significantly higher than that in refractory GD patients and NC group (P = 0.01; P = 0.007). The percentage of CD4+IL-36α+T cells in newly diagnosed GD patients was significantly higher than that in NC group (P = 0.030). In GD group, recombinant human IL-36α stimulation resulted in the increase of INF-γ, TNF-α, IL-6 and IL-17A (P = 0.015; P = 0.016; P = 0.039; P = 0.017). Conclusion: IL-36α and CD4+IL-36α+T cells may be involved in the pathogenesis of GD by promoting the production of Th1, Th2 and Th17 cytokines.